2013
DOI: 10.1111/trf.12348
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion complications in thalassemia patients: a report from the Centers for Disease Control and Prevention (CME)

Abstract: Background and Study Objectives Transfusions are the primary therapy for thalassemia but have significant cumulative risks. In 2004, the Centers for Disease Control and Prevention (CDC) established a national blood safety monitoring program for thalassemia. The purpose of this report is to summarize the patient population as well as previous non-immune and immune transfusion complications at the time of enrollment into the program. A focus on factors associated with allo- and auto-immunization in chronically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 62 publications
7
110
0
4
Order By: Relevance
“…RBC transfusions also prove to be life saving for acute sickle-related complications, such as acute ischaemic stroke, acute chest syndrome (ACS), splenic sequestration and aplastic crisis. However, transfusion of RBCs is complicated by development of allo-and auto-antibodies, which occur much more frequently in patients with SCD than in any other heavily transfused patient population (alloimmunization rates 18-47% for SCD vs. 7-19% for thalassaemia major (Rosse et al, 1990;Heddle et al, 1995;Hoeltge et al, 1995;Aygun et al, 2002;Castro et al, 2002;Azarkeivan et al, 2011;Thompson et al, 2011;Vichinsky et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…RBC transfusions also prove to be life saving for acute sickle-related complications, such as acute ischaemic stroke, acute chest syndrome (ACS), splenic sequestration and aplastic crisis. However, transfusion of RBCs is complicated by development of allo-and auto-antibodies, which occur much more frequently in patients with SCD than in any other heavily transfused patient population (alloimmunization rates 18-47% for SCD vs. 7-19% for thalassaemia major (Rosse et al, 1990;Heddle et al, 1995;Hoeltge et al, 1995;Aygun et al, 2002;Castro et al, 2002;Azarkeivan et al, 2011;Thompson et al, 2011;Vichinsky et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Transfusion reactions (some fatal) due to alloantibodies were well documented in the older literature. Unfortunately due to differences in ethnicity in donors and recipients of transfusions, alloimmunization will undoubtedly continue to persist even in modern times [26]. A recent survey found that, even in the industrialized world, the practice of transfusion medicine is still variable and could be improved and standardized to reduce alloimmunization [27].…”
Section: Prolonging Survival: Transfusions and Chelationmentioning
confidence: 99%
“…Transfusion transmitted diseases have dealt a lifelong blow to patients who began receiving transfusions prior to testing for hepatitis and/or HIV. In the industrialized world, these are either the oldest patient cohort or immigrants who began their transfusion history in countries where testing for pathogens is not yet standard practice [26]. Besides their immediate impact on the patient's health, transfusion transmitted infections can lead to late complications such as cirrhosis and/or hepatocelluar carcinoma (HCC).…”
Section: Prolonging Survival: Transfusions and Chelationmentioning
confidence: 99%
“…It must also be appreciated that splenectomy has many potential adverse immunologic and hematologic/vascular sequelae [109,110] beyond RBC immune responses to RBC antigens, especially over the long term. The human literature concerning the spleen's role in RBC alloimmunization is mixed: some studies have found that splenectomy has no statistically significant impact on RBC alloimmunization rates, or that it decreases alloimmunization [13,111,112,113], while others suggest that splenectomy may increase RBC alloimmunization rates [32,33,114,115]. Such findings are likely due in part to the large number of confounding variables involved and, as above with animal studies, may be affected by the history of RBC transfusion and whether the recipient was first exposed to foreign RBCs before or after splenectomy.…”
Section: Recipient Factorsmentioning
confidence: 99%
“…Young recipient age at the time of initial RBC exposure has been shown to influence rates of RBC alloimmunization in patients with sickle cell disease [14,79] and thalassemia major [115], leading to a hypothesis that relative ‘tolerance' to RBC antigens may be possible in young transfusion recipients. To date, only one animal study has been published investigating the relationship between recipient age at initial RBC exposure and RBC alloimmunization, with no or very low levels of anti-HOD alloantibodies observed in juvenile animals (3 weeks of age) compared to adult animals [80].…”
Section: Recipient Factorsmentioning
confidence: 99%